Singing off the same hymn sheet? Examining coherence in a talent development pathway (part 2) - Curran, O.; Passmore, D.; MacNamara, A. (Journal of Sports Sciences, 2022)
Existing literature highlights the common characteristics of successful talent development environments, notably the need for long-term development, individual athlete attention, communication, alignment, and psycho-behavioural development. Little is known however about the complex talent development environment of an international sport organisation where multiple contexts and various stakeholders exist. Considering the lack of research relating to females in talent development, we examined a female national hockey talent development environment and more specifically the level of coherence that existed within the talent development environment from different stakeholder perspectives. Twenty-seven international female hockey players and fourteen pathway staff members from across the talent development pathway participated in semi-structured focus groups. An inductive-deductive thematic analysis was conducted. Results suggest that the talent development environment provides a long-term development experience supplemented with individual athlete attention at international level. However, a general lack of coherence and systematic development was evident across the talent development environment contexts with varying levels of coherence found within the higher-order themes of appropriate development, not early success, individualised and ongoing development, and wide-ranging coherent messages and support. This highlights a need for improved direction from the National Governing Body if systematic coherence towards talent development is to be achieved.